Rh(III)-catalyzed, 1, 2, 3-triazole-assisted directed CH coupling with diazo diphosphonates. Issue 29 (18th July 2018) - Yu, Zhu-Jun; Zhang, Chen; Li, Jiang-Lian; Liu, Yan-Zhao; Yu, Xin-Ling; Guo, Li; Li, Guo-Bo; Wu, Yong
Graphical abstract: Highlights: 1, 2, 3-Triazole was used as the direct group for CH carbenoid coupling reactions. A step- and atom economical protocol constructing CC bond was developed. Bisphosphonates motifs, a unique pharmacophore, were easily assembled to arenes. Abstract: A mild and efficient procedure was developed for the [Cp∗Rh(III)]-catalyzed, 1, 2, 3-triazole directed CH coupling with diazomethylene-diphosphonates. This protocol provided a step- and atom-economical protocol for CC bond formation and led to structurally diverse 2-(1, 2, 3-triazol-2-yl)benzyl diphosphonates in good to excellent yields.